Evidence for reverse causality in the association between blood pressure and cardiovascular risk in patients with chronic kidney disease - Herrington, W; Staplin, N; Judge, P; Mafham, M; Emberson, J; Haynes, R; Wheeler, D; Walker, R; Tomson, C; Agodoa, L; Wiecek, A; Lewington, S; et al. (American Heart Association, 2016)
Among those with moderate-to-advanced chronic kidney disease, the relationship between blood pressure and cardiovascular disease appears ‘U’-shaped, but is loglinear in apparently healthy adults. The Study of Heart and Renal Protection randomized 9270 patients with chronic kidney disease to simvastatin/ezetimbe versus matching placebo, and measured blood pressure at each follow-up visit. Cox regression was used to assess the association between blood pressure and risk of cardiovascular disease among:(i) those with a self-reported history of cardiovascular disease; and (ii) those with no such history and, based on plasma troponin-I concentration, a low probability of subclinical cardiac disease. 8666 participants had a valid baseline blood pressure and troponin-I measurement and 2188 had at least one cardiovascular event during follow-up. After adjustment for relevant confounders, the association between systolic blood pressure and cardiovascular events was ‘U’-shaped, but among participants without evidence of prior cardiovascular disease, there was a positive loglinear association throughout the range of values studied. Among those with the lowest probability of subclinical cardiac disease, each 10mmHg higher systolic blood pressure corresponded to a 27% increased risk of cardiovascular disease (hazard ratio 1.27, 95% confidence interval 1.11-1.44). In contrast, the relationship between diastolic blood pressure and cardiovascular risk remained ‘U’-shaped irrespective of cardiovascular disease history or risk of subclinical disease. In conclusion, the lack of a clear association between systolic blood pressure and cardiovascular risk in this population appears attributable to confounding, suggesting that more intensive systolic blood pressure reduction may be beneficial in such patients.